Investigating Optical and Electronic Properties of GaAsBi for Photovoltaics - Lenney, Samuel. (Tufts University. Tisch Library., 2020)
Thesis (M.S.)--Tufts University, 2020.; Submitted to the Dept. of Electrical Engineering.; Advisor: Thomas Vandervelde.; Committee: Kevin Grossklaus, and Marc Hodes.; Keyword: Electrical engineering.; While silicon photovoltaics have come to dominate the commercial market for solar panels, a major area of research on photovoltaic (PV) technology seeks to maximize efficiency by exploring alternate semiconductor materials. Multijunction solar (MJ-PV) cells made from III-V semiconductor alloys have shown the ability to convert solar energy to electrical energy at much higher efficiency than traditional single-junction cells made from Si. These higher efficiency solar cells enable light to electrical conversion of higher intensity light sources, in part because the added efficiency reduces energy lost to heat. This benefit is critical for space PV applications where cells are subject to solar radiation that is not filtered by an atmosphere, as well as concentrated photovoltaic systems where solar radiation is focused using mirrors or lenses onto the solar cell. In this thesis, we characterize the optical and electronic properties of gallium arsenide bismide (GaAsBi), a III-V material which shows promise for MJ-PV applications. Current state of the art three-layered MJ-PV devices are discussed to motivate the development of a material with a 1 eV bandgap compatible with an InGaP/InGaAs/Ge device architecture. GaAsBi optical properties are characterized using variable angle spectroscopic ellipsometry. We show that the bandgaps of GaAs_(1-x)Bi_(x) samples with 0.031 ≤ x ≤ 0.065 are in a range relevant to MJ-PV, with the bandgap of x = 0.065 at 1.04 eV. Interband transitions above the bandgap of GaAsBi are observed and compared to observations in the literature. Creating a device using GaAsBi will require an understanding of the material's behavior when doped. To explore GaAsBi doping, N-type GaAsBi films doped with Te are annealed at varying temperatures and subsequently characterized by Hall effect to show electronic properties. It is shown that annealing Te doped GaAs_(1-x)Bi_(x=0.02) at 350 °C for 10 minutes increases carrier mobility by 30% relative to unannealed films. The results of this thesis can aid in further development of this material system with the end goal incorporating it into improved MJ-PV devices.